Origen's references to Heracleon a quotation-analytical study of the earliest known commentary on the gospel of John - Berglund, Carl Johan 1973-; Uppsala universitet (Tübingen Mohr Siebeck, 2020)
Cover -- Title -- Preface -- Table of Contents -- Figures -- Chapter 1: Introduction -- A. Aims and Questions -- B. Material -- C. Method -- D. Theoretical Framework -- I. "Gnostics" and "Gnosticism" -- II. "Valentinians" and "Valentinianism" -- III. The Heterodox and "Those Who Bring in the Natures" -- E. Previous Scholarship -- I. Groundwork -- II. Convergence -- III. Consensus -- IV. Reorientation -- V. Resistance -- VI. Reevaluations -- Chapter 2: Ancient Literary Criticism -- A. Greco-Roman Education and Learned Culture -- B. Principles of Ancient Literary Criticism -- C. Literary-Critical Commentaries -- D. Early Christian Commentaries -- E. Origen's Use of Literary Criticism -- F. Origen's Reception of Heracleon -- Chapter 3: Quotation Analysis -- A. Ancient Quotation Practices -- I. Quotations Adapted to New Contexts -- II. Quotations from Well-Known Literature -- III. Reconstructing Lost Works from Quotations -- IV. Quotations in Clement of Alexandria -- V. Quotations in Eusebius of Caesarea -- B. Origen's Quotation Practices -- I. Verbatim Quotations -- II. Summaries -- III. Explanatory Paraphrases -- IV. Mere Assertions -- C. Conclusion -- Chapter 4: Creators and Creations -- A. Passage 1: The Agency of Creation (John 1:3a) -- B. Passage 2: Spiritual Humans and Spiritual Life (John 1:3b-4) -- Chapter 5: The Testimony of John the Baptist -- A. Passage 3: The Explanation of the Only-Begotten (John 1:16-18) -- B. Passage 4: A Prophet Who Is Not the Prophet (John 1:21b) -- C. Passage 5 A: The Word, the Voice, and the Sound (John 1:23) -- D. Passage 5 B: What Is Around John Is Not John Himself (John 1:21) -- E. Passage 5 C: The Investigating Priests and Levites (John 1:19) -- F. Passages 6-7: John's Reason for Baptizing (John 1:24-27) -- G. Passage 8: Christ's Physical Presence (John 1:26-27).
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift